2012
DOI: 10.1029/2011gl049831
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of elves and lightning during El Niño and La Niña

Abstract: [1] We analyzed the ISUAL-FORMOSAT2 elves, the LIS-TRMM lightning, the sea surface temperature (SST), and the El Niño southern oscillation (ENSO) indices (the Niño 3.4 Index and the Southern Oscillation Index -SOI) in the period between June 2005 and May 2010 to explore the impacts of ENSO on the occurrences of the mesospheric elves and the troposphere lightning. The standardized anomalies of the elve and the lightning occurrence densities are used to quantify the deviation of the elve and lightning occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
(30 reference statements)
0
13
0
1
Order By: Relevance
“…These results suggest that the Kuroshio transport has gradually become stronger and more stable over the past 100 years. Previous climate model studies and reanalyzed observation data also showed the warming and acceleration of the western boundary currents resulting from the intensified wind stress curl from increased atmospheric CO 2 [ Wu et al , ; Sakamoto et al , ; Saenko et al , ]. The North Pacific Subtropical Gyre, including the Kuroshio Current, is driven by the westerly jet and trade wind on the ridge of the Hadley cell.…”
Section: Resultsmentioning
confidence: 98%
“…These results suggest that the Kuroshio transport has gradually become stronger and more stable over the past 100 years. Previous climate model studies and reanalyzed observation data also showed the warming and acceleration of the western boundary currents resulting from the intensified wind stress curl from increased atmospheric CO 2 [ Wu et al , ; Sakamoto et al , ; Saenko et al , ]. The North Pacific Subtropical Gyre, including the Kuroshio Current, is driven by the westerly jet and trade wind on the ridge of the Hadley cell.…”
Section: Resultsmentioning
confidence: 98%
“…This result implies that no additional correction for the variation of detection capability is needed for the statistical analyses of the TLE global occurrence rate and distribution reported by Chen et al (2008), , as well as the studies of the ISUAL recorded lightning Wu et al 2010). …”
Section: Impact Of the Effective Gain Changementioning
confidence: 86%
“…[] for the WWLLN lightning in 2010. This difference may come from year‐to‐year variations resulting from, for example, El Niño and La Niña events [ Sátori et al ., ; Wu et al ., ], or the variable detection efficiency of the network as more stations are added. Previous studies [ Barrington‐Leigh and Inan , ; Cheng et al ., ; Kuo et al ., ; Chen et al ., ] have indicated that TLEs, especially elves, are caused by energetic lightning.…”
Section: Energies Of Typical and Tle‐producing Lightningmentioning
confidence: 99%